1985
DOI: 10.1016/s0006-3495(85)83849-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence monitoring of rapid changes in membrane potential in heart muscle

Abstract: The rising phase of rat cardiac action potentials was measured in physiological solutions using the voltage-sensitive dye RH 237. A newly designed optical system and an argon ion laser for excitation allowed measurements without averaging over small areas (20-90 microns diameter) with high time resolution (response time 10-90%, 0.12 ms). The mean value of the fractional change in the fluorescence signal was approximately 3%/100 mV. The signal-to-noise ratio was approximately 60 rms (spot diameter 70 microns) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Thus, 2PLSM provides a sensitive measurement of physiologic events in the ms range, but the scan rate may be insufficient for accurately resolving fast events in the sub-ms range. Here, this affected the ability to resolve AP upstrokes in rodents; a <1ms event, as indicated by the microelectrode measurements and as previously reported [20]. Thus, the temporal resolution of the current 2PLSM protocols is not comparable to sampling rates offered by e.g.…”
Section: Sequential Ap and Ca 2+ Recordings By 2plsmmentioning
confidence: 75%
See 1 more Smart Citation
“…Thus, 2PLSM provides a sensitive measurement of physiologic events in the ms range, but the scan rate may be insufficient for accurately resolving fast events in the sub-ms range. Here, this affected the ability to resolve AP upstrokes in rodents; a <1ms event, as indicated by the microelectrode measurements and as previously reported [20]. Thus, the temporal resolution of the current 2PLSM protocols is not comparable to sampling rates offered by e.g.…”
Section: Sequential Ap and Ca 2+ Recordings By 2plsmmentioning
confidence: 75%
“…Initial spectral characterization of Ca 2+ -sensitive dyes (data not shown) confirmed that Fura-2 was both excitable with 2PLSM and presented with emission spectra discernible from Di-4-ANEPPS, such that intracellular Ca 2+ and V m could be measured without cross-contamination of voltage and Ca 2+ signals. As the 1P Fura-2 excitation spectrum is in the ultraviolet range with an absorption shift caused by changes in free Ca 2+ [16,20], we obtained 2P excitation spectra of Fura-2 at both high (60μmol/L) and low (>1nmol/L) free Ca 2+ , and compared these to the doubled 1P spectra (1Px2). As seen in Supporting figure 2A(ii), the absorption shift produced by high Ca 2+ also leads to a leftward shift in the 1Px2 spectra.…”
Section: Comparison Of 2p Excitation and Microelectrode Ap And Voltagmentioning
confidence: 99%
“…In the context of cardiac electrophysiology research, a major breakthrough in experimental techniques was the introduction of optical mapping of voltagesensitive dyes to tissue-level studies (Cohen & Salzberg 1978;Dillon & Morad 1981;Windisch et al 1985;Fast & Kléber 1993;Efimov et al 1994). This offered two key advantages over traditional electrical mapping techniques: (i) the recorded signal is proportional to the main quantity of interest, the transmembrane voltage, V m , and (ii) optical maps can be recorded immediately before, during and after the application of interventions, such as electrical shocks, with no lag time and without the overwhelming artefacts present in electrical recordings due to electrode polarization induced by strong electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution of a measurement is determined by both, the size of a measuring spot and its distance to the adjacent ones, as well as the depth in the specimen, in which fluorescence light is emitted and contributes thus to the optical signal. In our experiments we used surface staining throughout [4], which limited the depth of fluorescence to about 40 µm [1].…”
Section: A Methodological Aspectsmentioning
confidence: 99%